Strategy of the Latin American Thoracic Association (ALAT). Ten Strategic Goals for Development in 2016–2020 (2016)
Introduction Respiratory Health in Latin America faces great challenges. Prevalence and impact of respiratory diseases have been increasing in morbidity. Mortality rates have been rising in the region1 and respiratory medicine practice has been developing in a very fast and disorganized way. Our health systemand institutions are inefficient and fragmented. The Human Resources are insufficient and not well trained.2,3 Ensuring a successful and sustainable development of the respiratory medical specialty in this context is a priority for the Latin American Thoracic Association (Asociación Latinoamericana de Tórax – ALAT).4 Twenty years after its foundation, ALAT proposes an institutional strategy for 2016–2020. This project was led by the President and the General Secretary at a first meeting in Panama City on the 4th and 5th of December 2014 and additional sessions during 2015. It broughttogether the members ofthe Executive Committee, directors ofthe committees in charge of Science and Research, Education, International Relations, Congress, members of the Scientific Departments, Past Presidents, Members of ALAT’s staff and external consultants (Fig. 1). Participants were instructed to visualize the future challenges of ALAT and to propose initiatives, goals and plans that were to be presented to the group with a view on how to implement them successfully. Using methodologies and tools generally accepted in strategic business development,5 and taking into consideration successful case stories from related societies,6,7 the work done enabled the group to redefine the mission and the vision of ALAT. It also enabled the group to propose an integrated strategic plan composed of ten strategic goals.